Painful Blisters of Left Hand Following Extravasation of Remdesivir Infusion in COVID-19 - Kumar, Neeraj (Indian J Crit Care Med, 2021)
How to cite this article: Kumar N, Kumar A, Pradhan S, Kumar A, Singh K. Painful Blisters of Left Hand Following Extravasation of Remdesivir Infusion in COVID-19. Indian J Crit Care Med 2021;25(2):240–241.